2016
DOI: 10.1159/000443796
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms in Bitter Taste Receptor Genes and Clinical Features in Korean Asthmatics

Abstract: Background: Bitter taste receptors (TAS2R) in human airway smooth muscle have recently been shown to have an important role in bronchodilation, together with β2-adrenergic receptors. Object: To evaluate the association between genetic variations in TAS2R and clinical features, including bronchodilator response and asthma control. Method: We analyzed the association between single nucleotide polymorphisms (SNPs) of TAS2R10 and TAS2R14 and variables such as demographic data, atopy, duration of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…We also need to carefully assess the therapy effect of bitter tastants for different individuals, considering there may be big differences in genetic expression types and abundance of TAS2Rs from person to person (Yoon et al, 2016). It is also well known that children are more sensitive to bitter tastants than adults (Mennella et al, 2014).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…We also need to carefully assess the therapy effect of bitter tastants for different individuals, considering there may be big differences in genetic expression types and abundance of TAS2Rs from person to person (Yoon et al, 2016). It is also well known that children are more sensitive to bitter tastants than adults (Mennella et al, 2014).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…They are also related to disease outcomes (asthma control, CRS severity) and display significant heterogeneity, which affects their function. For example, genetic variations were associated with lower asthma control and better bronchodilator response (91). T2R38 genetic polymorphism predisposes to infection in upper airways via decreased NO production from epithelial cells in response to bacterial products (84).…”
Section: Figure 2 the Dynamic And Complex Interaction Between Risk Fmentioning
confidence: 99%
“…The extent to which polymorphisms of individual TAS2Rs impact the functionality of cells associated with the respiratory system is poorly understood. Polymorphisms in TAS2Rs have been linked to chronic rhinosinusitis (CRS), which is an inflammatory disorder of the nose and paranasal sinuses and in asthma (Adappa et al, 2013; Gallo et al, 2016; Yoon et al, 2016). Some have shown that the rs10246939 SNP ( TAS2R38 nucleotide 296 to valine) and other TAS2R polymorphisms are associated with CRS (Adappa et al, 2013; Mfuna et al, 2014; Cohen, 2017).…”
Section: Receptor Polymorphisms Disease Association and Development mentioning
confidence: 99%
“…However, others have demonstrated a lack of an association of haplotypes between CRS patients, either with (CRSwNP) or without (CRSsNP) nasal polyps, (Gallo et al, 2016). However, at least one study strongly supports identification of polymorphisms in TAS2Rs as possible genetic markers to predict outcomes in asthma (Yoon et al, 2016). Although these association studies have identified a possible link between TAS2R polymorphisms and respiratory diseases, a causal link is yet to be established and the specific contribution toward physiological process remains to be defined.…”
Section: Receptor Polymorphisms Disease Association and Development mentioning
confidence: 99%